Human Development X: Explanation of Macroevolution Top-Down Evolution Materializes Consciousness. The Origin of Metamorphosis - Tyge Dahl Hermansen; Søren Ventegodt; Joav Merrick (The Scientific World Journal)
In this paper, we first give a short discussion of the macroevolution viewing life as information-directed, complex, dynamic systems. On this basis, we give our explanation of the origin of life and discuss the top-down evolution of molecules, proteins, and macroevolution. We discuss these subjects according to our new holistic biological paradigm. In view of this, we discuss the macroevolution of the organism, the species, the biosphere, and human society. After this, we discuss the shift in evolution from natural selection to a new proposed process of nature called the metamorphous top-down evolution. We discuss the capability of the evolutionary shift to govern some of the processes that lead to the formation of new species. We discuss the mechanisms we think are behind this proposed shift in evolution and conclude that this event is able to explain the huge biological diversity of nature in combination with evolutionary natural selection. We also discuss this event of nature as an isolated, but integrated, part of the universe. We propose the most important genetic and biochemical process that we think is behind the evolutionary shift as a complicated symbiosis of mechanisms leading to metamorphosis in all biological individuals, from bacteria to humans. The energetic superorbital that manifests the consciousness governs all these processes through quantum chemical activity. This is the key to evolutionary shift through the consciousness, and we propose to call this process adult human metamorphosis.